2012
DOI: 10.1002/ccd.23391
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of cephalad arteries percutanoeus transluminal angioplasty with stent implantation (The CAPTAS registry)

Abstract: CAS is safe and successful procedure with low early and long-term adverse events. Special attention should be put on patients with bilateral and left ICA stenoses. If possible, longer stents should be applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Severe bias presence led to study exclusion from further analysis. Finally, CAS data from103 observational and 9 randomized studies were included [ 4 , 21 , 22 , 23 , 26 , 27 , 30 , 35 , 39 , 41 , 44 , 45 , 56 , 58 , 65 , 66 , 84 , 89 , 91 , 92 , 97 , 104 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ,…”
Section: Methodsmentioning
confidence: 99%
“…Severe bias presence led to study exclusion from further analysis. Finally, CAS data from103 observational and 9 randomized studies were included [ 4 , 21 , 22 , 23 , 26 , 27 , 30 , 35 , 39 , 41 , 44 , 45 , 56 , 58 , 65 , 66 , 84 , 89 , 91 , 92 , 97 , 104 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ,…”
Section: Methodsmentioning
confidence: 99%
“…However, guidelines are inconclusive 5 and the debate on carotid stent design in relation to clinical outcomes, occurrence of new MR-DWI lesions or restenosis, is ongoing. [6][7][8][9][10][11][12][13][14][15][16][17] This meta-analysis evaluated the effect of carotid stent design on early and late clinical adverse events as well as radiological outcomes in patients undergoing CAS for significant carotid artery stenosis, to allow for optimal evidence-based clinical decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Low incidence of adverse events after stenting has been shown in several single and multicenter clinical practice studies [2][3][4][5][6]. One of the latest trials to date, Carotid Revascularization Endarterectomy vs. Stenting Trial (CREST) demonstrated comparable outcome rates after stenting and surgery.…”
Section: Introductionmentioning
confidence: 99%
“…4,2 %. Věk ≥ 80 let zvyšoval riziko vzniku CMP/úmrtí z KV příčin/IM do jednoho roku (OR 4,41; 95% CI 1,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)36; p = 0,04). Závěry: Studie prokázala přijatelné klinické výsledky pacientů s CAS a vysokou incidencí přidružených onemocnění, kteří byli léčeni intenzivní farmakoterapií.…”
unclassified